MICRO AND NANO-AUTOLOGOUS FAT TRANSFER UNTUK TATA LAKSANA LIPODISTROFI WAJAH PADA LUPUS ERITEMATOSUS SISTEMIK - Batubara, Irwan Saputra; Suseno, Lis Surachmiati; Sitohang, Irma Bernadette; Legiawati, Lili (Media Dermato-Venereologica Indonesiana, 2024)
Introduction: Lipodystrophy in systemic lupus erythematosus (SLE) causes deformity and psychological problem for patients. The recommended treatment is autologous fat transfer (AFT) because of its effectiveness. Case: A 19-year-old woman with facial lipodystrophy due to SLE was treated with AFT. Fat tissue was aspirated from the lateral side of the left thigh and then processed into microfat and nanofat using the Luer-Lok connectors. The total volume of fat injected was 28 mL with a significant improvement of skin contour. She was satisfied with the results. There were no postoperative complications. She is still under monitoring for the next six months to assess AFT retention. Discussion: There are various modifications of the AFT technique to improve outcomes and avoid complications. Microfat aims to fill the volume loss, whereas nanofat is beneficial to improve skin contours. The main drawback of AFT is the unpredictable retention of fat volume. Patient factors, fat processing methods, and AFT technique play a role in post-AFT retention. Although extremely rare, fat embolization can occur during AFT which can be fatal. Injection with a blunt cannula, use of vasoconstrictors, and mapping of facial vascularization may reduce the risk of fat embolization. Conclusion: Autologous fat transfer is recommended for lipodystrophy because it is easy to perform, inexpensive, and non-immunogenic. Dermato-venereologists have an important role in the management of lipodystrophy due to SLE.